2020
DOI: 10.3390/ijerph17228633
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Training Can Make a Difference: Tools to Overcome the Impact of COVID-19 on Primary Schools. An Experimental Study

Abstract: Overcoming the impact of the coronavirus pandemic (COVID-19) on primary schools is an emerging need and priority in the current social welfare system. Accordingly, this study presents an empirical learning package to support teachers, who perform frontline work in schools, in coping with stress, preventing burnout, improving their information and communications technology (ICT) competency, and introducing the principles of emotional intelligence (EI) in the classroom. The participants included 141 primary scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 136 publications
9
51
0
6
Order By: Relevance
“…Our study is also in line with another study that the interactive course keeping and design of practical classes depend on individual tutor's creativity (Pozo-Rico, Gilar-Corbí, Izquierdo, & Castejón, 2020). At the beginning of the pandemic period, the majority of tutors experimented and transformed the practical classes, according to their design of teaching.…”
Section: Discussionsupporting
confidence: 89%
“…Our study is also in line with another study that the interactive course keeping and design of practical classes depend on individual tutor's creativity (Pozo-Rico, Gilar-Corbí, Izquierdo, & Castejón, 2020). At the beginning of the pandemic period, the majority of tutors experimented and transformed the practical classes, according to their design of teaching.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study assessed the efficacy of information and communications (ICT) technology training program on teacher’s stress and burnout levels during COVID-19 pandemic. The study that was conducted on primary school teachers is Spain found that participants in the training showed a decreased stress and burnout levels and an increase in the emotional intelligence levels [ 25 ]. While these studies showed promising results, in specific contexts, there is a scarcity of research on the effectiveness of blended interventions that combine offline and online sessions for improving teachers’ well-being and resilience during critical events and crises, such as the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers further mentioned that computer information literacy, communication and collaboration, and problem-solving skills are the most developed competencies, whereas digital content creation and security are the weakest [11]. Therefore, it is imperative that academic professional modernize, as in some cases some professionals may not be as familiar with recent technology [3,10,12]. The most underestimated problem during this pandemic continues being work overload that academic professionals endure on a daily basis, which is exacerbated, if they are not prepared because of technology impairdness, additionally there are those who, due to the nature of their work require going at least partially, which implies the continuous use of PPE, and the combination of preparing material at a distance and in person [2,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative that academic professional modernize, as in some cases some professionals may not be as familiar with recent technology [3,10,12]. The most underestimated problem during this pandemic continues being work overload that academic professionals endure on a daily basis, which is exacerbated, if they are not prepared because of technology impairdness, additionally there are those who, due to the nature of their work require going at least partially, which implies the continuous use of PPE, and the combination of preparing material at a distance and in person [2,12,13]. As a result, this leads to physical exhaustion, emotional fatigue and the fear of infection by contact with students or other teachers or someone in their family becoming infected, which causes even more anxiety and stress [14][15][16].…”
Section: Introductionmentioning
confidence: 99%